Do Fair Bets Exist? Direct Utility Functions Under Uncertainty - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
Some aspects of decision taking under risk are examined. The existence of fair gambles whose price equals their expected values is questioned and in addition the origin of expected utility is analysed.Then a diverse approach to decision taking under risk is considered, whereby agents maximize a utility function of consequences of actions. Consequences are treated like different goods and prospect is like a budle of goods. Stochastic dominance is invoked as a second stage criterion to decide whether to accept or not a prospect. Even though some problems arise as to the continuity by using the indirect utility function we are able to explain the Allais Paradox.
Keywords: 330